2018
DOI: 10.1007/s10144-018-0607-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic divergence among island populations of sika deer (Cervus nippon) in southern Japan: a test of the local adaptation hypothesis

Abstract: Transplant and common garden experiments have been used in studies on local adaptation, but are diicult to be conducted for large animals with long life span. A previous study on the southern Japanese islands demonstrated that relative limb lengths of sika deer (Cervus nippon) were short on islands with steep slopes. We hypothesized that this morphological variation was evidence for local adaptation, and tested this hypothesis by comparing phenotypic divergence with neutral genetic divergence among eight popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
(65 reference statements)
2
8
0
Order By: Relevance
“…Sato et al (2017) reported such populations of wood mice ( Apodemus speciosus ) on Hakatajima island, the haplotype diversity of which diverged from the general relationship between haplotype diversity and island size. A similar pattern was observed in sika deer ( Cervus nippon ) on Yakushima island (Table S1, Terada & Saitoh, 2018). The nested population structure hypothesis predicts that the structure of populations with higher haplotype diversity is more complex than that of those with standard haplotype diversity.…”
Section: Discussionsupporting
confidence: 78%
“…Sato et al (2017) reported such populations of wood mice ( Apodemus speciosus ) on Hakatajima island, the haplotype diversity of which diverged from the general relationship between haplotype diversity and island size. A similar pattern was observed in sika deer ( Cervus nippon ) on Yakushima island (Table S1, Terada & Saitoh, 2018). The nested population structure hypothesis predicts that the structure of populations with higher haplotype diversity is more complex than that of those with standard haplotype diversity.…”
Section: Discussionsupporting
confidence: 78%
“…The next step of life history evolution would be illustrated by the Yakushima Island deer, which also showed slower growth rate and intermediate histological features, coupled by a moderate shift of survivorship curve toward those of K -selected species. Contrary to the situation of the Kerama deer, the slower growth rate of Yakushima deer is considered to have a genetic basis because 1) Yakushima deer are not malnourished and have enjoyed a recent population increase [43] and 2) some of their macromorphological features have a genetic basis [44, 45]. A long-term field observations of Yakushima deer also supported our finding that the life history traits of this population is shifting to K -strategist (Agetsuma and Agetsuma-Yanagihara, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Yakushima Island was possibly connected to Kyushu Island by a land bridge during the Last Glacial Maximum (ca. 25,000 ya), but the genetic differentiation between the two populations implies a much longer period of isolation for Yakushima deer (Nagata et al 1999, Terada andSaitoh 2018). The complete skeleton of each individual has been stored at Tochigi Prefectural Museum (TPM), Utsunomiya, Japan.…”
Section: -1 Extant Taxamentioning
confidence: 99%
“…The body size of Yaku sika deer is considerably smaller than other subspecies of Japanese sika deer (e.g., Kyushu sika deer [ C. n. nippon ], Honshu sika deer [ C. n. centralis ], Ezo sika deer [ C. n. yesoensis ]; Whitehead ). Terada () showed that the dwarfing of Yaku sika deer was genetically linked, potentially because of food limitation from high population density through predator release (Kay , Lomolino ). Under these food limitation conditions, deer may have evolved the ability to detoxify phenolics to expand the range of foods they can consume.…”
Section: Discussionmentioning
confidence: 99%